Coaching In Business is A Factor Determining The Increase In Efficiency And Effectiveness of Modern Managers - Miroslaw BETKOWSKI (Communications of International Proceedings, 2022)
Looking for modern methods of increasing the effectiveness and efficiency of today's employee teams, we are looking for solutions that fit the possibilities of modern management. Many management models can be used in educational and strategic systems. Human and his ability to react to the changing environment are the most important factors in achieving the effectiveness of their activity. Each change creates a new challenge but also shapes man's natural resistance to the unknown. The resistance to change is the more, the greater the risk of successful implementation and the number of undefined elements are. In a such circumstances, coaching is one of the tools facilitating and streamlining the introduction of a system that increases efficiency. In the article, the author will present the concept of coaching as well as the Business Coaching model and tools that allow for its implementation. The substantive considerations will be analyzed by means of a questionnaire examining the level of preparation of the staff of trainers, managers, employees and people taking the role of a manager. The possibility of shaping attitudes of individual managers and employee teams, whose are using the elements and tools of coaching in business will be presented.
Keywords: coaching in business; efficiency; effectiveness; Models of Business Coaching